Exosome-Contained APOH Associated With Antiphospholipid Syndrome - Tan, Yuan; Bian, Yiding; Song, Yunfeng; Zhang, Qinhua; Wan, Xiaoping (Frontiers in Immunology, 2021)
BACKGROUND: Antiphospholipid syndrome (APS) is a systemic autoimmune disease that can lead to thrombosis and/or pregnancy complications. Exosomes, membrane-encapsulated vesicles that are released into the extracellular environment by many types of cells, can carry signals to recipient cells to affect angiogenesis , apoptosis, and inflammation. There is increasing evidence suggesting that exosomes play critical roles in pregnancy. However, the contribution of exosomes to APS is still unknown. METHODS: Peripheral plasma was collected from healthy early pregnancy patients (NC-exos) and early pregnancy patients with APS (APS-exos) for exosome extraction and characterization. The effect of exosomes from different sources on pregnancy outcomes was determined by establishing a mouse pregnancy model. Following the coincubation of exosomes and human umbilical vein endothelial cells (HUVECs), functional tests examined the features of APS-exos. The APS-exos and NC-exos were analyzed by quantitative proteomics of whole protein tandem mass tag (TMT) markers to explore the different compositions and identify key proteins. After incubation with HUVECs, functional tests investigated the characteristics of key exosomal proteins. Western blot analysis was used to identify the key pathways. RESULTS: In the mouse model, APS-exos caused an APS-like birth outcome. In vitro experiments showed that APS-exos inhibited the angiogenesis and invasion of HUVECs. Quantitative proteomics analysis identified 27 upregulated proteins and 9 downregulated proteins in APS-exos versus NC-exos. We hypothesized that apolipoprotein H (APOH) may be a core protein, and the analysis of clinical samples was consistent with finding from the proteomic TMT analysis. APOH-exos led to APS-like birth outcomes. APOH-exos directly enter HUVECs and may play a role through the phospho-extracellular signal-regulated kinase pathway. CONCLUSIONS: Our study suggests that both APS-exos and APOH-exos impair vascular development and lead to pregnancy complications. APOH-exos may be key actors in the pathogenesis of APS. This study provides new insights into the pathogenesis of APS and potential new targets for therapeutic intervention.